A weak-inversion low-power active mixer for 2.4 GHz ISM band applications - Boon, Chirn Chye (2010)
This work describes a fully integrated active mixer designed in 0.18µm CMOS technology for 2.4 GHz Industrial, Scientific and Medical (ISM) band applications. The mixer uses a source driven local oscillator (LO) to integrate the RF-LO buffering with the active mixer, and weakly inverted input MOSFETs to improve the gain and noise performance. The double-balanced quadrature mixer has a measured conversion gain of 32 dB with a double sideband (DSB) noise figure (NF) of 8.5 dB at 30 MHz intermediate frequency (IF) while consuming only 0.56 mA of current from a 1.8 V supply.